'"These Findings Confirm Conclusions Many Have Arrived at by Intuition or Common Sense": Water, Quantification and Cost-effectiveness at the World Bank, ca. 1960 to 1995'. (19th April 2020) - McMillen, Christian
Abstract: Providing clean water and sanitation was based on the common-sense notion that each had obvious benefits. Overcoming uncertainty, achieving precision, and quantifying the effects of clean water and sanitation came to dominate thinking on water and sanitation in the 1980s. As cost effectiveness analysis infiltrated global health the broad goal of providing clean water and adequate sanitation diminished in importance as short term solutions like Oral Rehydration Therapy prevailed. Seeking cost-effective solutions to large scale problems in global health while also wanting to quantify their benefits has common-sense appeal. But when it comes to water and sanitation cost effectiveness analysis has confronted at least one insurmountable challenge: quantifying the benefits of water and sanitation is, and has always, been notoriously difficult. It is intuitive that clean water and adequate sanitation contribute to good health. Quantifying the effects, as we will see, are all but impossible.